Transcranial magnetic stimulation and intravenous ketamine combination therapy for treatment-resistant bipolar depression: A case report - Elkrief, Laurent; Payette, Olivier; Foucault, Jean-Nicolas; Longpré-Poirier, Christophe; Richard, Maxime; Desbeaumes Jodoin, Véronique; Lespérance, Paul; Miron, Jean-Philippe (Frontiers in Psychiatry, 2022)
About a third of patients suffering from major depression develop treatment-resistant depression (TRD). Although repetitive transcranial magnetic stimulation (rTMS) and intravenous ketamine have proven effective for the management of TRD, many patients remain refractory to treatment. We present the case of a patient suffering from bipolar TRD. The patient was referred to us after failure to respond to first- and second-line pharmacotherapy and psychotherapy. After minimal response to both rTMS and ketamine alone, we attempted a combination rTMS and ketamine protocol, which led to complete and sustained remission. Various comparable and complimentary mechanisms of antidepressant action of ketamine and rTMS are discussed, which support further study of this combination therapy. Future research should focus on the feasibility, tolerability, and efficacy of this novel approach.